A modified stress-strain relation for austenitic stainless steels at cryogenic temperatures. (July 2019) - Ding, Huiming; Wu, Yingzhe; Lu, Qunjie; Wang, Yibo; Zheng, Jinyang; Xu, Ping
Highlights: Higher martensitic transformation rate is responsible for the shape transformation of S30408 with temperature decreasing. A modified stress-strain relation for austenitic stainless steels at cryogenic temperatures is proposed. Proposed relation shows a reasonable fitness with experimental results at 77–293 K. Abstract: Low-temperature stress-strain relation of austenitic stainless steels (ASS) is essential for understanding the performance of pressure vessel at cryogenic temperatures. This paper experimentally investigated the stress-strain relation of ASS S30408 in a wide range of 77–293 K by quasi-static tensile tests. A significant strain-induced martensitic transformation is observed during the plastic deformation, which results into a change in the shape of stress-strain curve from a parabola to an inverted 'S'. However, the Ludwigson stress-strain relation, which is widely used for ASS at 300–1023 K, cannot be used to characterize the low-temperature deformation of S30408 with martensitic transformation, because it does not rationally consider the influence of martensitic transformation on deformation. To precisely describe the stress-strain relation at cryogenic temperatures, a modified Ludwigson relation is proposed based on the assumption that the mechanical work difference between experimental curve and fitted Ludwigson curve is linearly proportional to martensite content. It is found that the proposed relation shows a good fitness with low-temperature experimental results. Furthermore, when no martensitic transformation occurs, the proposed relation transfers to the original Ludwigson relation, which means that the proposed relation has a wide applicability from cryogenic temperatures to high temperatures. Additionally, the proposed relation can also be used for different types of ASS and shows a significant potential application in design and safety assessment of ASS structures.